HUBUNGAN NEGARA HUKUM DENGAN HAM DI INDONESIA - Hutabarat, Dany Try Hutama; Lutfianur, Bunga Cyntia; Amsari, Duwi Anggun; Nadila, Irvi; Yani, Cindy Indah; Kartika; Rizki, Alfathi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Laws are regulations made by the government. The rule of law is a state that enforces justice that deviates from the rules of a country. Human rights (HAM) can be interpreted as basic rights in humans. Human rights have been given since we were born, so no one has the right to rob human rights, whoever it is. The rule of law is enforced so that people can obey the rules of a country, one of which is to protect one's human rights. The rule of law with human rights is very attached. Because one indication to be called a state of law, among others, the enforcement of human rights, because a state of law without respecting and respecting the principles of human rights cannot be called a state of law